Pengaruh Penerapan Sistem Modernisasi Administrasi Perpajakan terhadap kepatuhan wajib pajak pratama Kabupaten Majene - dahlia dahlia (Program Studi Akuntansi Syariah, 2025)
AbstractThe purpose of this study is to determine the effect of implementing the Tax Administration Modernization System on the compliance of primary taxpayers in Majene Regency. This type of research is quantitative. The data analysis technique used is simple linear regressionThe result of the research is that the implementation of the Tax Administration Modernization System variable has a positive and significant influence on the compliance of primary taxpayers in Majene Regency.